Regulatory Cross-Talks and Cascades in Rice Hormone Biosynthesis Pathways Contribute to Stress Signaling - Deb, Arindam; Grewal, Rumdeep K.; Kundu, Sudip (Frontiers in Plant Science, 2016)
Crosstalk among different hormone signaling pathways play an important role in modulating plant response to both biotic and abiotic stress. Hormone activity is controlled by its bio-availability, which is again influenced by its biosynthesis. Thus independent hormone biosynthesis pathways must be regulated and co-ordinated to mount an integrated response. One of the possibilities is to use cis-regulatory elements to orchestrate expression of hormone biosynthesis genes. Analysis of CREs, associated with differentially expressed hormone biosynthesis related genes in rice leaf under Magnaporthe oryzae attack and drought stress enabled us to obtain insights about cross-talk among hormone biosynthesis pathways at the transcriptional level. We identified some master transcription regulators that co-ordinate different hormone biosynthesis pathways under stress. We found that Abscisic acid and Brassinosteroid regulate Cytokinin conjugation; conversely Brassinosteroid biosynthesis is affected by both Abscisic acid and Cytokinin. Jasmonic acid and Ethylene biosynthesis may be modulated by Abscisic acid through DREB transcription factors. Jasmonic acid or Salicylic acid biosynthesis pathways are co-regulated but they are unlikely to influence each other’s production directly. Thus multiple hormones may modulate hormone biosynthesis pathways through a complex regulatory network, where biosynthesis of one hormone is affected by several other contributing hormones.